Shear Salvation - Julian Smith (Symphony in the Flint Hills, 2015)
At the edge of the world, the wind is strong enough to make you stumble, and it never seems to stop. Constant gusts batter the southernmost tip of Argentina, just across the Strait of Magellan from Tierra del Fuego, where sheep graze on gently rolling grasslands as whitecaps race across the South Atlantic. The story of sheep rancher's routine and how the life of the grassland impacts the people around it.
Keywords: grassland; wind; environment; ecosystem; species; animals; plants; trees; diversity; danger; life; conservation; preserve; progress; desertification; biodiversity; ecological; ranching; farmer; farm; plant; herds; holistic